PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PELUANG DI KELAS XI IPA-1 MAN 1 KEBUMEN - Juwariyah, Mutiyatun (STAI Darul Qalam Tangerang, 2025)
The background of this problem is student learning outcomes in low mathematics subjects, especially opportunity material, the lack of student involvement in the learning process tends to be passive, the models used in the learning process are also less varied, so that it has an impact on student learning outcomes. The formulation of the problem in this study is whether the application of the Jigsaw cooperative learning model to the opportunity material can improve the mathematics learning outcomes of class XI IPA-1 students of MAN 1 Kebumen. This type of classroom action research (CAR) uses Kurt Lewin's theory. It was carried out at the MAN 1 Kebumen, with research subjects in class XI IPA-1, totaling 21 students. Data collection instruments are tests and observations. The PTK procedure starts from the planning, action, observation and reflection stages. This research was conducted in II cycles, each cycle of 2 meetings. The results showed that applying the Jigsaw cooperative learning model to opportunity material could improve the mathematics learning outcomes of class XI IPA-1 students at MAN 1 Kebumen. This is proven based on the results of data analysis obtained in the first cycle of the first meeting which obtained an average student score of 66.4 with a completeness percentage of 28% and at the second meeting the student's average score became 73 with a percentage of 43%. Then there was an increase in the third meeting of cycle II where the average score of students was 77 with a completeness percentage of 57% and at the fourth meeting it also increased to 86% with an average of 82. From the data analysis, the researcher stated that this research was successful with a percentage of student completeness is 86% and achieves an average score of ≥ 75